Pengaruh Chief Executive Officer (CEO) Gender dan Independensi Dewan Komisaris Terhadap Earnings per Share (EPS) Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2025 - Muhammad Fakhri Saputra; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of CEO gender and board independence on corporate financial performance, measured by Earnings per Share (EPS). The study utilizes data from manufacturing companies listed on the Indonesia Stock Exchange, comprising a total of 504 observations. Panel data regression analysis is employed to investigate the relationship between corporate governance characteristics and financial performance. The results indicate that CEO gender has a negative and significant effect on EPS, suggesting that firms led by female CEOs tend to exhibit lower EPS compared to those led by male CEOs. Furthermore, board independence is also found to have a negative and significant effect on EPS. These findings imply that an increase in the proportion of independent commissioners does not necessarily enhance a firm's earnings per share. The results support the Upper Echelons Theory, which posits that executives’ characteristics and corporate governance mechanisms influence strategic decision-making processes and organizational outcomes. This study provides practical implications for companies and stakeholders in understanding the effectiveness of leadership structure and corporate governance mechanisms in improving financial performance.